Zwicky Transient Facility and Globular Clusters: The gr-band Period–Luminosity Relations for Mira Variables at Maximum Light and their Applications to Local Galaxies - C.-C. Ngeow; Jia-Yu Ou; Anupam Bhardwaj; Josiah Purdum; Ben Rusholme; Avery Wold (The Astronomical Journal, 2023)
Based on 14 Miras located in seven globular clusters, we derived the first gr -band period–luminosity (PL) at maximum light for the large-amplitude Mira variables using the multiyear light-curve data collected from the Zwicky Transient Facility (ZTF). Since Miras are red variables, we applied a color-term correction to subsets of ZTF light curves, and found that such corrections do not have a large impact on period determinations. We applied our derived PL relations to the known extragalactic Miras in five local galaxies (Sextans, Leo I, Leo II, NGC 6822 and IC 1613), and determined their Mira-based distances. We demonstrated that our PL relations can be applied to short-period (≲300 days) Miras, including those in the two most distant galaxies (NGC 6822 and IC 1613) in our sample even when only a portion of the light curves around maximum light have detections. We have also shown that the long-period extragalactic Miras do not follow the PL relations extrapolated to longer periods. Hence, our derived PL relations are only applicable to the short-period Miras, which will be discovered in abundance in local galaxies within the era of Vera C. Rubin Observatory’s Legacy Survey of Space and Time.